2015
DOI: 10.1007/s13365-015-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

Macaque species susceptibility to simian immunodeficiency virus: increased incidence of SIV central nervous system disease in pigtailed macaques versus rhesus macaques

Abstract: Immune pressure exerted by MHC class I-restricted cytotoxic T cells drives the development of viral escape mutations, thereby regulating HIV disease progression. Nonetheless, the relationship between host immunity and HIV central nervous system (CNS) disease remains poorly understood. The simian immunodeficiency virus (SIV) macaque model recapitulates key features of HIV infection including development of AIDS and CNS disease. To investigate cell-mediated immunity regulating SIV CNS disease progression, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…With this inoculation combination, approximately two-thirds of macaques develop SIV encephalitis within 84 days 156,157 . Of interest is the fact that, though most studies of SIV pathogenesis use rhesus macaques, pigtailed macaques develop CNS disease more often than do rhesus macaques that receive the same SIV inoculum 158 . Key features of the pigtailed macaque SIV model include development of CNS inflammation that correlates with high viral load in the brain, cognitive and motor deficits typical of HIV, and the classic lesions of HIV encephalitis 156,159163 .…”
Section: Animal Models Of Neuro-hivmentioning
confidence: 99%
“…With this inoculation combination, approximately two-thirds of macaques develop SIV encephalitis within 84 days 156,157 . Of interest is the fact that, though most studies of SIV pathogenesis use rhesus macaques, pigtailed macaques develop CNS disease more often than do rhesus macaques that receive the same SIV inoculum 158 . Key features of the pigtailed macaque SIV model include development of CNS inflammation that correlates with high viral load in the brain, cognitive and motor deficits typical of HIV, and the classic lesions of HIV encephalitis 156,159163 .…”
Section: Animal Models Of Neuro-hivmentioning
confidence: 99%
“…Additionally, using SIVsm804E the authors demonstrated both MHC-I and TRIM5alpha as restrictive host genotypes, underscoring both the role of viral sequences as well as host viral restriction factors in SIVE development[10]. Similar restrictive host genetic MHC I alleles, were reported by Beck et al, in pig tail macaques [8]. These factors underscore the importance of innate anti-viral factors within macrophages, as well as CTL responses most likely against SIV-gag proteins.…”
Section: Viral Sequence Sequence Evolution and Neuroaidsmentioning
confidence: 60%
“…Historically early models used rhesus macaques (RM) or pigtail macaques (PM) and different viral clones or swarms that resulted in immune suppression (AIDS) macrophage tropism for CNS infection, and SIV encephalitis (SIVE) in approximately 30 percent of the animals in RM and higher percentages of PM [8](Table 1). More recently, immune modulation (depletion) of CD4 and CD8 T lymphocytes, and/or serial passage of virus through monkeys for enhanced macrophage replication and neurotropism have been used [6,911] (Table 1).…”
Section: Non-human Primate Models Of Neuroaidsmentioning
confidence: 99%
“…, 2002), specific end points were predetermined according to stage of disease [acute phase at 7 and 10 days post infection (dpi), asymptomatic phase at 21, 35, 42, and 56 dpi, and terminal AIDS at 84 dpi]. Because the course of disease progression is more variable in rhesus macaques, these animals were euthanized when two or more AIDS-defining criteria were met (mean length of infection 213 days)(Beck et al , 2015). …”
Section: Methodsmentioning
confidence: 99%